Grazing behavior and dietary preferences of sheep grazing a Mediterranean rangeland - Manousidis T.; Iatridou S.; Lempesi A.; Kyriazopoulos A.P. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Shepherds manage the feeding and grazing system of their flocks in order to achieve the coverage of animals’ nutritional requirements and to maximize their productivity. The present study aimed to assess sheep grazing behavior and forage selection throughout the year, in order to provide useful information for the shepherds’ management decisions. For this purpose, a flock of 250 Chios crossbreed sheep grazing in a hilly Mediterranean rangeland in Northern Greece was used. Grazing behavioral data was recorded using the direct observation method during three seasons (spring, summer and autumn). Measurements included the number of bites per functional plant group (grasses, forbs and woody plants) consumed by sheep. The animal’s behavioral activities (feeding, walking and resting) were also recorded and analysed. Significant differences in dietary preferences were observed among the seasons. Grasses were selected mainly in spring and autumn at a rate significantly higher (60.3% and 54.2%, respectively) than summer whereas forbs were preferred in summer. Woody species were not consumed in spring whereas their contribution to sheeps’diet significantly increased in summer and autumn (21.4% and 20.5%, respectively) when the availability of herbaceous vegetation was reduced. Feeding was the main activity on the rangeland, represented an average of 70.4% of the recorded activities. Walking lasted significantly longer in autumn and resting time increased in summer probably due to the higher temperature. Despite the fact that sheep select mainly herbaceous species, woody vegetation is considered as an important forage source during the periods with low availability of herbaceous forages and it complements sheep nutrient intake.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)